The Admissibility of Online Poker Games in the Polish Legal System versus Protective Legislation - Frańczuk, Magdalena; Knurowska, Iwona (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
In the paper we analyse amendments to the Gambling Act of 19 November 2009 (OJ 2009, no. 201, item 1540, as amended) concerning the playing of online poker games in the context of laws and institutions protecting potential players. We argue that the absence of such regulation was replaced by a blanket ban on online gambling, which the legislature perceives as a preventive measure. The paper focuses on an analysis of the gap that came to light during a review of the amended provisions of the Gambling Act. The gap consists in a lack of either regulation or indeed institutions protecting potential gamers-consumers, especially minors but also those that have an impaired perception of the actions they take, against the consequences of gambling. The legislature's rationale in enforcing a prohibition is of particular interest. The paper also looks at sample protective institutions in selected European countries.